Single inhaler triple therapy (SITT) in asthma: Systematic review and practice implications. Issue 4 (15th September 2021) - Agusti, Alvar; Fabbri, Leonardo; Lahousse, Lies; Singh, Dave; Papi, Alberto
Abstract: A significant number of patients with asthma remain uncontrolled despite treatment with inhaled corticosteroids (ICS) and long‐acting β2 adrenergic bronchodilators (LABA). The addition of long‐acting antimuscarinic agents (LAMA) can improve the management of asthma in these patients. Recently, three novel triple therapy (ICS/LABA/LAMA) formulations in a single‐inhaler device (SITT) have been investigated in patients with uncontrolled asthma despite ICS/LABA treatment. Here, we review systematically the evidence available to date in relation to SITT in patients with uncontrolled asthma despite ICS‐LABA treatment and conclude that SITT is a safe and effective therapeutic alternative in these patients. We also discuss how to position this new therapeutic alternative in their practical clinical management as well as the opportunities and challenges that it may generate for patients, physicians, and payers.